Individual differences in peace of mind reflect adaptive emotion regulation - Sikka Pilleriin; Revonsuo Antti; Gross James J. (Elsevier Ltd, 2025)
Well-being consists of several different dimensions, such as hedonic and eudaimonic well-being. However, peace of mind (PoM)—an aspect of well-being characterized by internal peace and harmony—has only recently begun to receive attention. It has been shown that PoM predicts important outcomes, such as depression and anxiety. An open question is what underlies individual differences in PoM. One important factor may be emotion regulation. However, to date, no studies have been conducted on PoM and emotion regulation. Here, we investigated the relationship between individual differences in PoM and trait emotion regulation. In two studies, participants from Finland (Study 1, N = 417) and the US (Study 2, N = 303) completed measures of PoM, trait emotion regulation, and other aspects of well-being and ill-being. Results showed that people with higher levels of PoM displayed a greater tendency to use cognitive reappraisal and a lesser tendency to use expressive suppression. Our findings suggest that adaptive emotion regulation may play an important role in explaining PoM and may serve as a promising target for interventions designed to enhance PoM.